PENGARUH PEMBERDAYAAN DAN KUALITAS PEGAWAI NEGERI SIPIL TERHADAP EFEKTIVITAS ORGANISASI PADA SEKRETARIAT DAERAH KABUPATEN TIMOR TENGAH UTARA - Elfrida Desiderata Naihati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research was explanatory research. It’s explained about the influence of free variabel, such as empower of civil servant (X1) and quality of civil servant (X2) concerning with effectiveness of organization in secretariat TTU regency. The population in this research was 153 civil servant under the scope of secretariat TTU regency with 9 parts. The techniques used in this research was random sampling. The data taken from questioness and it’s analysed used descriptive statistic and infferencial analysis statistic. The result of descriptive analysis show that, the variabel empower with indicator achievement was 73,57%, the quality variabel of civil servant was 70,64% and the effectiveness organization was 73,71%. Based on the third variabel respondent was good. The result of inferencial analysis showed that, coefficient determinate with value R2 was 0,769 means that contributed empower variabel (X1) and quality civil servant (X2) with effectivenessof organisation in secretariat TTU regencywas 76,9% and remainded from the other variabel but not in this research. The result of test hypothesis partial variabel in empower and quality of civil servant about effectiveness organisation with empower variabel value was 0,009. Variabel quality of civil servant was 0,000 and the significant value simultan was 0,000 where the value of the thirdsignificant < from alfa 0,05 or 5%.